Bandwidth-Efficient Cooperative Relaying Schemes with Multiantenna Relay. (14th May 2008) - Ho-Van Ho-Van, Khuong Khuong; Le-Ngoc Le-Ngoc, Tho Tho
Abstract : We propose coded cooperative relaying schemes in which all successfully decoded signals from multiple sources are forwarded simultaneously by a multiantenna relay to a common multiantenna destination to increase bandwidth efficiency. These schemes facilitate various retransmission strategies at relay and single-user and multiuser iterative decoding techniques at destination, suitable for trade-offs between performance, latency, and complexity. Simulation results show that the proposed schemes significantly outperform direct transmission under the same transmit power and bandwidth efficiency.